Digging up the remains - Henry, Julia, 1962- (Henry, Julia, 1962- Garden Squad mystery, 2020)
"Between hosting a haunted house on her lawn, serving on the town's 400th Anniversary Planning Committee, and prepping for the Fall Festival's 10k fundraiser, Lilly's hands are full. She doesn't have time for prickly newspaper reporter Tyler Crane, who's been creeping around town, looking for dirt on Goosebush's most notable families ... until he's found dead on the race route moments before the start. An unfortunate accident? Or did Tyler unearth a secret that someone in Goosebush is willing to kill to keep? By planting nasty rumors and cultivating fear, Tyler sowed a fair share of ill will during his brief time in town. Weeding through the suspects will be thorny, but Lilly and her Garden Squad are determined to root out the autumnal assassin before the Fall Festival flops . . ."--Publisher description